Highly Conductive PEDOT:PSS Nanofibrils Induced by Solution‐Processed Crystallization. (16th December 2013) - Kim, Nara; Kee, Seyoung; Lee, Seoung Ho; Lee, Byoung Hoon; Kahng, Yung Ho; Jo, Yong‐Ryun; Kim, Bong‐Joong; Lee, Kwanghee
<x xml:space="preserve">Abstract</x> Crystalline poly(3, 4‐ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS) nanofibrils with an electrical conductivity of 4380 S cm‐1 are formed via a solution process using H2SO4. The concentrated H2SO4 treatment induces a significant structural rearrangement of the PEDOT:PSS via a charge‐separated transition mechanism, resulting in highly ordered and densely packed PEDOT:PSS nanofibrils. The PEDOT:PSS electrode shows a sheet resistance of 46 Ω sq‐1 with 90% optical transmittance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>